Regulation of dipeptide transport in Saccharomyces cerevisiae by micromolar amino acid concentrations. - Island, M D (1987)
Prototrophic Saccharomyces cerevisiae X2180, when grown on unsupplemented minimal medium, displayed little sensitivity to ethionine- and m-fluorophenylalanine-containing toxic dipeptides. We examined the influence of the 20 naturally occurring amino acids on sensitivity to toxic dipeptides. A number of these amino acids, at concentrations as low as 1 microM (leucine and tryptophan), produced large increases in sensitivity to leucyl-ethionine, alanyl-ethionine, and leucyl-m-fluorophenylalanine. Sensitivity to ethionine and m-fluorophenylalanine remained high under either set of conditions. The addition of 0.15 mM tryptophan to a growing culture resulted in the induction of dipeptide transport, as indicated by a 25-fold increase in the initial rate of L-leucyl-L-[3H]leucine accumulation. This increase, which was prevented by the addition of cycloheximide, began within 30 min and peaked approximately 240 min after a shift to medium containing tryptophan. Comparable increases in peptidase activity were not apparent in crude cell extracts from tryptophan-induced cultures. We concluded that S. cerevisiae possesses a specific mechanism for the induction of dipeptide transport that can respond to very low concentrations of amino acids.